(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The problem of the status of gender equality in Cameroon’s secondary educational programs and projects reveals, so to speak, a manifest insufficient enrolment of girls in STEM fields. The enrolment of boys continues to dominate that of girls. According to MINESUP Statistical Yearbooks, by 2021 the enrolment of girls into science subjects was 11,776 as opposed to 21,104 for boys. In industrial subjects, girls’ enrolment was 1,018 as opposed to boys’ enrolment of 4, 535. In relation to technical subjects a total number of 6,775 were enrolled as opposed to 7,262 for boys. This inequality that is depicted in the educational system since 2014 could have a major consequence of constituting a hindrance in achieving the objectives set by the government by 2035. Such will influence the non-fulfilment of governmental and international wishes. The educational policy on Science, Technology, Engineering and Mathematics (STEM) considered as a factor of development represents all the commitments or orientations covering the actions of government of a given society. The case of Cameroon is based on a set of international conventions and national legislations and is guided principally by the 1998 law of orientation on education that applies to nursery, primary, post-primary, secondary general, technical and teacher training and the 2001 law of orientating of higher education in Cameroon.